Analysis of the relationship between the syndrome of frailty and cognitive deficit in older adults with independent living - Da Cunha, Gilson Luis (2017)
Abstract: Elderly frailty is a syndrome composed of motor and metabolic factors and aspects of cognitive decline. The objective of this work was to evaluate the relationship between indicators of frailty and cognitive deficit in older adults with independent life, living in the city of Ivoti, Rio Grande do Sul State, Brazil. This study had a cross-sectional quantitative design, considering sociodemographic variables, cognitive status, and frailty syndrome components. Inclusion criteria were to have 65 years, understand the instructions, agree to participate and be a permanent resident at home and census tract. Data were analyzed using Pearson's bivariate correlation test. The results showed 15 correlations between frailty and other variables of the study, 9 of them also occur in the cognitive deficits and 6 are present only in the frailty syndrome. Cognitive deficit and frailty syndrome are not mutually exclusive in the subjects studied, but influence each other. In this study, 27 variables were tested for correlation with frailty and cognitive deficit. 21 of them were correlated to cognitive deficit. 15 were correlated to the frailty syndrome. This slight predominance of issues unrelated to the motor performance suggests psychosocial factors may have a significant impact on the establishment of the frailty syndrome.